Accounting for what and to whom? Accountability tensions in collaborations addressing long‐term unemployment. (7th August 2022) - Hansen, Magnus Paulsen; Triantafillou, Peter; Bellò, Benedetta; Boon, Jan; Doninck, Dries Van; Downe, James; Hopkins, Cate; Klijn, Erik Hans; Sarapuu, Külli; Stevens, Vidar; Verhoest, Koen
Abstract: Across Europe, public employment services are experimenting with more holistic and cross‐sector collaborations to tackle the wicked problem of long‐term unemployment. These collaborations operate in a context characterised by tensions produced by multiple demands for accountability. Based on case studies of the accountability relations and challenges in five such collaborations in the Netherlands, Belgium (Flanders), Estonia, Scotland and Denmark, we found that: rigorous use of quantifiable measurement regimes made it difficult to attribute salience to important aspects of the progress made by the unemployed citizen; standardised accounts come with the risk of reductionist understandings of the citizen's social circumstances and resources; superficial participation by local politicians resulted in rather weak political accountability and a marked ambiguity of the role of the client as both accountee and accountholder.